2019
DOI: 10.1002/adfm.201905806
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Ultrabroadband Phototransistor Based on Two‐Dimensional Bi2O2Se Nanosheets

Abstract: Bi2O2Se, a high‐mobility and air‐stable 2D material, has attracted substantial attention for application in integrated logic electronics and optoelectronics. However, achieving an overall high performance over a wide spectral range for Bi2O2Se‐based devices remains a challenge. A broadband phototransistor with high photoresponsivity (R) is reported that comprises high‐quality large‐area (≈180 µm) Bi2O2Se nanosheets synthesized via a modified chemical vapor deposition method with a face‐down configuration. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 56 publications
(40 reference statements)
0
55
0
Order By: Relevance
“…The EQE was calculated to be 1.3 × 10 5 % under 245 nm light, which is the highest among those obtained under wavelengths of light from 245 to 450 nm. Such a high EQE reveals an obvious high gain ( G ) of the device illuminated under the UV light 38–42. If the quantum efficiency (η) is ignored, the G is the same meaning as EQE , which is often produced by the prolonged carrier lifetime attributed to the defects of 2D materials 39.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The EQE was calculated to be 1.3 × 10 5 % under 245 nm light, which is the highest among those obtained under wavelengths of light from 245 to 450 nm. Such a high EQE reveals an obvious high gain ( G ) of the device illuminated under the UV light 38–42. If the quantum efficiency (η) is ignored, the G is the same meaning as EQE , which is often produced by the prolonged carrier lifetime attributed to the defects of 2D materials 39.…”
Section: Figurementioning
confidence: 99%
“…The value of θ decreases from 1.03 to 0.36 revealing the photoresponse mechanism changes from photoconduction effect to photogating effect by V g (Figure 6b). 38 Due to the enhancement of the photogating effect, the R λ value and EQE are increased up to 12 739.13 A W −1 (Figure 6c) and 6.46 × 10 6 % (Figure S8b, Supporting Information) with a high D * of 8.37 × 10 12 jones of at V g = 35 V. Moreover, the D * can be further increased from 10 12 to 10 14 Jones by controlling the V g (Figure S8c, Supporting Information). On the other hand, the photoconduction effect at V g of −40 V results in a fast photoresponse, as the −3 dB cut‐off frequency is increased from 735 Hz at 0 V to 3414 Hz at −40 V (Figure 6d), corresponding τ rise is decreased from 476 to 102 µs.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] Bismuth oxyselenide (Bi 2 O 2 Se), a semiconducting 2D material featured by narrow bandgap (≈0.8 eV), high electronic mobility (20 000 cm 2 V −1 s −1 at 2 K), and good air stability, shows great potential for applications in high-performance electronics, optoelectronics, and flexible devices. [4][5][6][7][8][9][10] For example, the photodetectors based on Bi 2 O 2 Se with ultrabroadband responses, [7] high on/off ratio, and ultrahigh photodetectivity [8] have been demonstrated. Bi 2 O 2 Se is also an important material to fabricate three-terminal memristors with high speed and low energy consumption for neuromorphic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al reported an infrared PD based on 2D Bi 2 O 2 Se, which demonstrated a high sensitivity of 65 A · W −1 at 1200 nm and ultrafast photoresponse of ~1 ps at room temperature ( Figure 6J) [171]. Through a modified CVD method, Tong et al synthesized large-area (≈180 μm) Bi 2 O 2 Se nanosheets and constructed PDs [54]. The photodetection wavelength of the device covers the UV-Vis-NIR range, and the R reaches 108,696 A · W −1 (at 360 nm), 50,055 A · W −1 (at 405 nm), 25,505 A · W −1 (at 532 nm), 843.5 A · W −1 (at 808 nm), 118 A · W −1 (at 1310 nm) and 22.12 A · W −1 (at 1550 nm).…”
Section: Bi 2 O 2 Sementioning
confidence: 99%
“…Thus, it is indispensable to focus on these novel materials to accelerate the synthesis process and the development of magnetic and spintronic applications. Among them, air-stable Bi 2 O 2 Se nanosheets with an ultralow electron effective mass (0.14 m 0 ) and a narrow bandgap (~0.8 eV) have exhibited extraordinary electron mobility (28,900 cm 2 · V −1 · s −1 at 2 K) and high on/off ratio (10 6 ) [54]. In contrast, the layer-by-layer interaction is electrostatic force instead of vdWs.…”
Section: Introductionmentioning
confidence: 99%